Koeksistensi Psoriasis Pustular Generalisata Dan Sistemik Lupus Eritematosus: Kasus yang Langka - Della Amanda; Muhammad Iqbal Fauzi; Teguh Priyanto (Jurnal Ners, 2025)
Introduction: Psoriasis and systemic lupus erythematosus (SLE) shares immunological and genetic risk factors. The coexistence of both conditions is extremely rare, with a prevalence of about 0.69%. The following case report outlines a rare case of generalized pustular psoriasis (GPP) coexisting with SLE and highlights the challenges in managing the patient. Case Report: A woman presented with complaints of pus-filled bumps all over her body. Her previous treatment history included methotrexate and cyclosporine for 2 years, and there were increased transaminase enzyme levels. Physical examination revealed pustules, patches, and erythematous plaques that are multiple and well-defined, and a positive lake of pus sign with a generalized distribution. The BSA score was 87% and the SLEDAI score was 10. The therapy administered was a 300 mg injection of secukinumab. Discussion: The coexistence of GPP and SLE is rare. The upregulation of Th1 and Th17 immune pathways can sustain chronic inflammation in both psoriasis and SLE. Managing such cases poses a challenge to clinicians. Methylprednisolone therapy for SLE may trigger psoriasis relapses, whereas phototherapy as an adjuvant therapy for psoriasis may lead to SLE flare-ups. The elevated transaminase enzyme levels in this patient also posed a challenge in appropriate therapy selection. Studies have shown an increase in IL-17 expression in patients with SLE and psoriasis. Administering biological agents that inhibit IL-17 may be considered as a therapy option for patients with psoriasis and SLE. Conclusion: The coexistence of GPP and SLE is a rare case and poses unique challenges in its management. Secukinumab may be considered as a therapeutic option for patients with GPP and SLE.